Antithrombotic activity of LB30057, a newly synthesized direct thrombin inhibitor - Kang, Kyu-Tae; Jung, Byoung-In; Bae, Ok-Nam; Lee, Moo-Yeol; Chung, Seung-Min; Lee, Joo-Young; Lee, Sang-Koo; Kim, In-Chul; Chung, Jin-Ho (Thrombosis and Haemostasis, 2003)
An amidrazonophenylalanine derivative, LB30057, inhibits the catalytic activity of thrombin potently by interaction with the active site of thrombin, and has high water solubility. In the present study, we evaluated the effect of LB30057 on the biological activities of thrombin at various tissues, and determined whether thrombin inhibition by LB30057 could reduce the incidence of occlusive thrombosis in an in vivo animal model. Treatment with LB30057 to human plasma prolonged clotting times in a concentration-dependent manner. LB30057 suppressed significantly thrombin-induced phosphatidylserine (PS) exposure in platelets, suggesting that LB30057 could inhibit blood coagulation accelerated by PS exposure. In human platelets, soluble thrombin- and clot-induced platelet aggregation was inhibited by LB30057 potently. Consistent with this finding, LB30057 showed concentration-dependent inhibitory effects on serotonin secretion and P-selectin expression induced by thrombin in platelets. In the blood vessel isolated from the guinea pig, treatment with LB30057 resulted in a concentration-dependent inhibition of thrombin-induced vascular contraction. In vivo study revealed that LB30057 following oral administration significantly increased the time to occlusion and improved carotid arterial patency using rat carotid artery thrombosis model. All these results suggest that LB30057 is a potent inhibitor of biological activities of thrombin at various target tissues and, therefore, might be developed as an anti-thrombotic agent for treatment and prevention of thrombotic diseases.
Keywords: Thrombin inhibitor; LB30057; antithrombotic activity